(untitled) (Journal of Educational Sciences, 2022)
The article provides a comprehensive analysis of traditional teaching methods, which are widely used in modern higher education, in a modern way. New conclusions were made about the history of the methodological field of modern pedagogical science, and the methodological heritage of Alash figures was analyzed. The author focuses on the complexity and problems of teaching the works of the great writer M. Auezov in higher education. New conclusions were drawn about the specificity and importance of starting the teaching of the works of the great writer in higher education with the use of new technologies from his fiction. The author speaks about the pedagogical contribution of M. Auezov to the science of literary criticism and methods of teaching literature. Considers ways to analyze the effectiveness of teaching the works of the writer in higher education. Provides a scientific study of the types of work that are effectively organized in the process of literary analysis. In the analysis of Auezov’s works it is recommended to refer to the image system of the work of art, the types of analysis in revealing the characters. The search for M. Auezov’s legacy and scientific works in innovative methods of teaching, the use of innovative teaching technologies is a modern requirement. Emphasizes the importance of fiction, our national values in the modern information society. Analytical work is offered in order to awaken students’ ability to read and express their views on the work of art in modern society. During the study of the author’s story "Karash-Karash okigasy" are analyzed the tasks that effectively lead students to cognitive work, the solution of the problem. The author offers an effective way of presenting the situation in the process of problem-based learning. The views, analyzes and conclusions of M. Auezov’s artistic narrative are clearly reflected in the new methodology of autonomy in the field of modern methodology. He also concludes that the writer’s legacy will last for centuries, and it is the duty of every teacher to pass it on to the younger generation. Key words: writer; innovative technology; teaching; methodology; story; literary analysis; literary text; methods.